Making better maize plants for sustainable grain production in a changing climate - Gong, Fangping; Wu, Xiaolin; Zhang, Huiyong; Chen, Yanhui; Wang, Wei (Frontiers in Plant Science, 2015)
Achieving grain supply security with limited arable land is a major challenge in the 21st century, owing to the changing climate and increasing global population. Maize plays an increasingly vital role in global grain production. As a C4 plant, maize has a high yield potential. Maize is predicted to become the number one cereal in the world by 2020. However, maize production has plateaued in many countries, and hybrid and production technologies have been fully exploited. Thus, there is an urgent need to shape maize traits and architectures for increased stress tolerance and higher yield in a changing climate. Recent achievements in genomics, proteomics and metabolomics have provided an unprecedented opportunity to make better maize. In this paper, we discuss the current challenges and potential of maize production, particularly in China. We also highlight the need for enhancing maize tolerance to drought and heat waves, summarize the elite shoot and root traits and phenotypes, and propose an ideotype for sustainable maize production in a changing climate. This will facilitate targeted maize improvement through a conventional breeding program combined with molecular techniques.